PEMANFAATAN TEKNOLOGI ARTIFICIAL INTELLIGENCE (AI) UNTUK ANALISIS TEKS VEDA: PENDEKATAN NLP DALAM STUDI ṚG VEDA MANDALA 1 SUKTA 1 - Eka Sura Adnyana; Gde Wikan Pradnya Dana; I Made Ade Prayoga (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2025)
This research discusses the utilization of Artificial Intelligence (AI) technology with a Natural Language Processing (NLP) approach in the study of Hindu literature, especially in the text of Ṛgveda Mandala 1 Sukta 1. The analysis was conducted through the stages of tokenization, lemmatization, and topic modeling to identify keywords, frequency of occurrence, and main themes in the text. The results found four central themes: (1) ritual (yajña), (2) theological (Agni's role as an intermediary between humans and gods), (3) spiritual and material goals (ratna), and (4) cosmic order (ṛta). AI  findings were then compared with traditional philological interpretations that emphasize philosophical meaning, symbolism, and historical context. The comparison results show that AI excels in speed, scale, and consistency of analysis, while traditional philology is stronger in providing depth of interpretation and understanding spiritual values. This study concludes that the integration of AI with the philological approach can result in a more comprehensive, rapid, and faithful study of the Vedas.